First record of the ant subfamily Aenictinae (Hymenoptera, Formicidae) from Saudi Arabia, with the description of a new species - Mostafa Sharaf; Abdulrahman Aldawood; Magdi El-Hawagry (ZooKeys, 2012)
The ant subfamily Aenictinae is recorded for the first time from the Kingdom of Saudi Arabia and for the second time from the Arabian Peninsula. A new species Aenictus arabicus sp. n., is described from the worker caste. Aenictus arabicus belongs to the A. wroughtonii-group and appears to be most closely related to A. rhodiensis Menozzi, but can be easily distinguished from the latter by the following characters: overall smaller size; cephalic index (head width/head length) small; occipital corners in lateral view rounded; antennal scape when laid back surpassing approximately two- thirds of head length; funicular segments 2–8 each at least 2× as long as broad; subpetiolar process well developed; petiole and postpetiole distinctly imbricate; gaster and clypeus entirely yellow, teeth of mandibles reddish- brown. Aenictus arabicus was collected from leaf litter, next to a tree of Psidium guajava L. The new species also is similar to A. sagei andA. wroughtonii. Affinities and a key to related species of the species group are given.